2005
DOI: 10.1111/j.1742-4658.2005.04554.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased NADPH concentration obtained by metabolic engineering of the pentose phosphate pathway in Aspergillus niger

Abstract: The pentose phosphate pathway (PPP) and glycolysis comprise the most central pathways in primary metabolism (Fig. 1). The PPP is believed to be the major source of NADPH required for many biosynthetic and detoxification reactions. The flux through this pathway has been reported to increase at high NADPH requirements, for Many biosynthetic reactions and bioconversions are limited by low availability of NADPH. With the purpose of increasing the NADPH concentration and ⁄ or the flux through the pentose phosphate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 49 publications
1
42
0
Order By: Relevance
“…Based on these findings, it was concluded that the accumulation of erythritol was due to excess activity of the PP pathway in excess compared with the cellular demand for the pathway intermediates (Röhr et al, 1987). Recently, Poulsen et al (2005) have also observed high PP pathway enzyme activities during stationary phase in A. niger. In the present work, the production yields of erythritol and arabitol increased during oxygen limitation when the biomass production was low and the production of CO 2 was high.…”
Section: Influence Of the Oxygen Availabilitymentioning
confidence: 90%
See 2 more Smart Citations
“…Based on these findings, it was concluded that the accumulation of erythritol was due to excess activity of the PP pathway in excess compared with the cellular demand for the pathway intermediates (Röhr et al, 1987). Recently, Poulsen et al (2005) have also observed high PP pathway enzyme activities during stationary phase in A. niger. In the present work, the production yields of erythritol and arabitol increased during oxygen limitation when the biomass production was low and the production of CO 2 was high.…”
Section: Influence Of the Oxygen Availabilitymentioning
confidence: 90%
“…For each glucose-6-phosphate entering the PP pathway two NADP molecules are reduced by the enzymes glucose-6-phosphate dehydrogenase and 6-phosphogluconate dehydrogenase. When nitrate is used as nitrogen source, an increase of these two enzyme activities has been noticed in A. nidulans and A. niger (Habison et al, 1983;Hankinson and Cove, 1972;Kinghorn and Unkles, 1994;Poulsen et al, 2005;Singh et al, 1988). More specifically, Poulsen et al (2005) have shown that, in A. niger, the activities of three enzymes belonging to the PP pathway increase when nitrate is added to the medium: glucose-6-phosphate dehydrogenase, 6-phosphogluconate dehydrogenase, and transketolase.…”
Section: Influence Of the Nitrogen Sourcementioning
confidence: 92%
See 1 more Smart Citation
“…Increasing the carbon flux through the PP pathway is often pursued (Chin et al, 2009;Lim et al, 2002;Poulsen et al, 2005;Skorupa Parachin et al, 2009) or proposed (Walton and Stewart, 2004) as a strategy to increase the efficiency of NADPH-dependent reactions in whole-cell systems. Our results indicate that while the Dpgi mutation improves the Y PPG (2.6-fold), this benefit is counterbalanced by a decrease in the specific in vivo activity of the biocatalyst (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although both strategies have been applied successfully in various prokaryotes, they are not effective in every organism [215,216]. Moreover, as mentioned above, G6PDH is a key enzyme not only for control of the PPP flux but also for control of the ED pathway.…”
Section: Introductionmentioning
confidence: 99%